2016
DOI: 10.1093/jpepsy/jsw016
|View full text |Cite
|
Sign up to set email alerts
|

Sleep Disturbance in Caregivers of Children With Respiratory and Atopic Disease

Abstract: Deficient and poor-quality sleep in caregivers of children with chronic illness may have a significant impact on their health and well-being, as well as caregiving responsibilities. These data provide important information for pediatric psychologists working with these families.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
63
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(68 citation statements)
references
References 35 publications
4
63
1
Order By: Relevance
“…[21] Thus, psychological stress and AD symptoms appear to form a vicious circle because the sleep disturbances experienced by AD patients result in inappropriate sleep quality and quantity and increase mental health problems, including psychiatric disorders. [14,2224] …”
Section: Discussionmentioning
confidence: 99%
“…[21] Thus, psychological stress and AD symptoms appear to form a vicious circle because the sleep disturbances experienced by AD patients result in inappropriate sleep quality and quantity and increase mental health problems, including psychiatric disorders. [14,2224] …”
Section: Discussionmentioning
confidence: 99%
“…Having a child with a chronic disease may also have a negative impact on a parent's well‐being. Indeed, numerous studies have reported that the parents of children affected by a large range of chronic diseases, such as atopic dermatitis, asthma, cystic fibrosis, neuromuscular diseases, autism, epilepsy and disabilities, suffer from impaired quality of sleep and quality of life, high levels of anxiety and depression and family problems . Moreover, it has been reported that parents who spend an average of one hour per night nursing their child have interrupted sleep, difficulties falling asleep and, as a consequence, chronic exhaustion .…”
Section: Introductionmentioning
confidence: 99%
“…Parents of children with AD were 4-8 times more likely to sleep less than 6 hours on average, have shorter sleep duration, and be more prone to insomnia when compared to the parents of healthy children, and exhibit clear signs of sleep disturbances (Meltzer & Booster, 2016). In Lee et al's study (2009), consistent short sleep durations of less than 6 hours were associated with increased risk of suicidal ideation.…”
Section: Discussionmentioning
confidence: 92%